PELUANG EFISIENSI PENGGUNAAN DAN BIAYA PUPUK PADA LAHAN SAWAH HASIL ANALISA TANAH (KASUS DI KECAMATAN MAOS KABUPATEN CILACAP) - Sodiq Jauhari; D Juanda JS (Agroland: Jurnal Ilmu-ilmu Pertanian, 2006)
The nutrient mapping objectivity is 1) Information and data can lowland on P and K nutrient, 2) Lowland cover account for level P and K status. The using impact is efficient and rational for P and K. Fertilizing recommended of paddy, the fertilizer need efficient is guiden soil nutrient status. Analysis program on the chemical element status of the ricefield P and K in 2003 is located in Maos Subdistrict of Cilacap Regency. Methodology use comprises: preparation, operation of soil sample taking and analysis of soil. Main Survey performs the sample talking of individual soil which is become as sample of comphosit sample, 1 sample of chomposit sample consist of 10- 15 sample of individual soil. The next level is sample of chomposit, show much 156 cohmposit soil, the data from the result of soil analysis of the content P and K through 3 status (low criteria, middle and high). Commonly.  The result of the status mapping on the ricefield P and K is as follows: there are 156 samples of soil of the chemical element status P; low up to high of Maos Subdistrict, the middle status is 31-38 mg/100 mg P2O5 or 735,052 hectars wide; and the high status is 50-77 mg / 100 g P2O5 with 1258,282 hectars wide, but the status of middle chemical element K is 14-18 mg/100 g P2O5 with 1.696,649 hectars wide and the status of high K is 22-37 mg/100 g K2O with 400,738 hectars wide by doing fertilizing suitable with the result of soil analysis, so the cost can be economized for Rp 370 259 63,-1 per season for the buying of the fertilizer SP-36 and Rp 35. 093.520 per planting season for the buying of the fertilizer KCL.